Isovitexin Depresses Osteoarthritis Progression via the Nrf2/NF-κB Pathway: An in vitro Study - Hu X (Dove Medical Press, 2021)
Xiaofen Hu,1,2,* Ruijie Li,1,2,* Ming Sun,1,2 Ying Kong,1,2 Haifeng Zhu,1,2 Fujiang Wang,1 Quanqing Wan1,2 1The Third Affiliated Hospital of Zhejiang Chinese Medicine University, Hangzhou, 310005, People’s Republic of China; 2Zhejiang Chinese Medical University, Hangzhou, Zhejiang Province, 310053, People’s Republic of China*These authors contributed equally to this workCorrespondence: Quanqing WanThe Third Affiliated Hospital of Zhejiang Chinese Medicine University, 219 Moganshan Road, Hangzhou, 310005, Zhejiang, People’s Republic of ChinaEmail 13003678819@163.comPurpose: Osteoarthritis (OA) is a multifactorial joint disease and inflammatory processes contribute to joint destruction. Isovitexin (IVX) is a flavone component found in passion flower, Cannabis and, and the palm that is known for its anti-inflammatory properties.Materials and Methods: This study investigated in vitro the role and underlying mechanism used by IVX in its regulation of OA development. Effects of IVX on the viability of chondrocytes were measured by CCK-8 assays. The phenotypes of extracellular matrix (ECM) degeneration and inflammation were measured by qPCR, Western blot, and ELISA; and NF-κB pathway was detected by immunofluorescence and Western blot. Molecular docking was applied to predict the interacting protein of IVX, while Nrf2 was knocked down by siRNAs to confirm its role.Results: We demonstrated that IVX suppressed ECM degeneration and suppressed pro-inflammatory factors in IL-1β-treated chondrocytes. Additionally, IVX impact on NF-κB signaling in IL-1β-exposed chondrocytic cells; Mechanistically, it was also demonstrated in molecular docking and knock down studies that IVX might bind to Nrf2 to suppress NF-κB pathway.Conclusion: Our data suggest that IVX halts OA disease advancement through the Nrf2/NF-κB axis, suggesting a possibility of IVX as a target for OA therapy.Keywords: osteoarthritis, isovitexin, extracellular matrix, NF-κB, Nrf2